Effect of fundamental variables on stock prices (studies on mining companies that go public on the Jakarta stock exchange) - Akhmad Nur Hidayah (Digital Business: Tren Bisnis Masa Depan, 2022)
This study aims to determine the effect of fundamental variables consisting of Debt To Equity Ratio (DER), Return On Equity (ROE), Dividend Per Share (DPS), Earning Per Share (EPS), and Price Earning Ratio (PER) on stock prices. The shares in question are shares of mining companies that go public on the Jakarta Stock Exchange. To find out the effect of fundamental variables on stock prices, multiple linear regression analysis was used. The results of the multicollinearity test showed that the DPS and EPS variables were collinear, so that the DPS variables were excluded from the regression model. The results of multiple linear regression analysis show that DER, ROE, EPS and PER simultaneously have a significant effect on stock prices. Then EPS partially has a significant and dominant influence on stock prices. This means that EPS is the main consideration for investors in investing in stocks, especially in mining companies. Therefore EPS can be used as input in predicting stock prices for investors and issuers. For investors who will invest, it is necessary to make EPS as a reference in making investment decisions. For issuers who want to increase their share price in the capital market, they can take steps to improve the company's performance by increasing their EPS because the company sells shares with the consequence that it must meet the investor's goal, namely to get maximum profit. This is the company's obligation to investors. If the investor's goals cannot be met, the company's credibility will decrease.